Social skills training for adolescents with general moderate learning difficulties - Cornish, Ursula (Jessica Kingsley Publishers, 2004)
Following the success of their many years' social skills work with children and adolescents with Asperger Syndrome and other moderate learning difficulties, Ursula Cornish and Fiona Ross have compiled a set of imaginative training sessions and workshops for teachers. Based on a multi-sensory cognitive-behavioural approach, the sessions cover pre- and post-intervention evaluation schedules, interview and observation tools, and specification of materials that can be used and adapted by teachers. With direct links to the four main stages of development at Key Stages 3 and 4 of the National Curric.